RANCANG BANGUN ALAT PENYEMPROTAN DISINFEKTAN OTOMATIS UNTUK MENCEGAH PENYEBARAN VIRUS CORONA - Rizal Nurhadi Gunawan; Teti Desyani (CV. Multi Kreasi Media, 2023)
The COVID-19 pandemic (Corona Virus Disease 2019) is caused by a corona virus called SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus). frequently touched, on contaminated surfaces and this is an important first step in the disinfection process. Disinfectant spraying can be done manually or automatically, automatic spraying is a very efficient and energy-saving method. The manufacture of this automatic disinfectant spraying device uses an ultrasonic sensor HC-SR04 and Arduino Modulo Uno R3 DIP Atmega328p as controllers. This tool is in the form of a spray using a hose that is tamped from a drum or bucket as the spray. It is used to sterilize PPE clothing (Personal Protective Equipment) used by health workers and people who work using PPE (Personal Protective Equipment).